1988
DOI: 10.2136/sssaj1988.03615995005200050054x
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Phosphate Precipitation in the Goethite/Phosphate System

Abstract: A combined scanning Auger, XPS, scanning SIMS, and TEM (electron diffraction) investigation of naturally‐occurring goethite surfaces in contact with 10−3 M KH2PO4 solution for 90 d at 60 °C has shown that isolated crystallites of the mineral griphite, Fe3Mn2(PO4)2.5(OH)2, are formed by reprecipitation from solution. No adsorbed phosphate can be detected on the goethite surface above 0.1 atomic % and there is no phosphate penetration of the goethite crystals. Evidence concerning initial adsorption of phosphate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 0 publications
0
41
0
1
Order By: Relevance
“…This slow uptake is thought to be the result of one or more of the following processes: i) diffusion to less accessible sites within pores of solid aggregates (Willet et al, 1988;Cabrera et al, 1981;Parfitt, 1989;Madrid and de Arambarri, 1985;Lookman et al, 1994); ii) penetration into the amorphous Fe and/or Al oxides by solid state diffusion (van Riemsdijk and de Haan, 1981;van Riemsdijk et al, 1984;Barrow, 1983); and iii) pre cipitation with metals derived by dissolution of the soil matrix (Aulenbach and Meisheng, 1988;Lookman et al, 1994;Martin et al, 1988;Nanzyo, 1984Nanzyo, , 1986Pierzynski et al, 1990). Malati et al (1993) reported that phosphate sorption on kaolinite, mica, and anatase at pH Ͻ 5 was endothermic and generally in the range of ϩ10 to ϩ15 kJ mol Ϫ1 .…”
Section: Phosphate Sorptionmentioning
confidence: 99%
“…This slow uptake is thought to be the result of one or more of the following processes: i) diffusion to less accessible sites within pores of solid aggregates (Willet et al, 1988;Cabrera et al, 1981;Parfitt, 1989;Madrid and de Arambarri, 1985;Lookman et al, 1994); ii) penetration into the amorphous Fe and/or Al oxides by solid state diffusion (van Riemsdijk and de Haan, 1981;van Riemsdijk et al, 1984;Barrow, 1983); and iii) pre cipitation with metals derived by dissolution of the soil matrix (Aulenbach and Meisheng, 1988;Lookman et al, 1994;Martin et al, 1988;Nanzyo, 1984Nanzyo, , 1986Pierzynski et al, 1990). Malati et al (1993) reported that phosphate sorption on kaolinite, mica, and anatase at pH Ͻ 5 was endothermic and generally in the range of ϩ10 to ϩ15 kJ mol Ϫ1 .…”
Section: Phosphate Sorptionmentioning
confidence: 99%
“…However, the images obtained by SIMS have a spatial resolution which did not allow us to test the hypothesis of a potential, subsequent diffusion of phosphate ions into the micro-or mesoporosity of Fe oxyhydroxides (Strauss et al 1997, Torrent et al 1994. Martin et al (1988) showed by SIMS analysis (depth profile) of a naturally occurring goethite sample exposed to 10 −3 M KH 2 PO 4 solution that there was no solid-state diffusion of phosphate into goethite. These authors also showed by TEM and electron diffraction that a metal phosphate mineral (griphite) precipitated on the goethite surface.…”
Section: Location Of Phosphorus On Goethite Particlesmentioning
confidence: 99%
“…Fe oxides seem to sorb phosphate by ligand exchange with surface OH groups monocoordinated with Fe atoms (Parfitt, 1978). However, other mechanisms, such as precipitation, cannot be excluded (Jonasson et al, 1988;Martin et aL, 1988). Synthetic goethites frequently have a phosphate sorption capacity of about 2.5/zmol P/m 2 at moderately acid to neutral pH values (Hingston, 1981;Cabrera et al, 1981;Borggaard, 1983a;Anderson et al, 1985;Torrent et al, 1990).…”
Section: Introductionmentioning
confidence: 99%